Effect of the 2016 International Rugby Union trial law amendments on the physical running demands of rugby union games: A pilot study - Curran, O. A.; Carling, C. (Journal of Australian Strength and Conditioning, 2018)
In September 2015 the IRB announced they would be trialling new law amendments in senior male rugby union during the 2016 Mitre 10 Cup Competition. Results from this study indicate that the amendments resulted in an increase in the running and speed demands of the game.